Şanlıurfa’da Halk Hekimliği - Şeker, Metin (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
The purpose of the trial is to bring out the methods of treatment of the Folk Medicine used in the ġanlıurfa region and to make the forgotten information with a written source permanent. Diseases have always been ongoing since the first man. People have tried many methods to produce these remedies. These methods are the basis of today's medical science. Some of the information conveyed from the beginning is still used despite the advanced medical science. For this reason the literacy rate is still not at the desired level and the health institutions are still not reaching some regions. Another reason is that modern medicine can not find the healing that our people are looking for. Today, folk medicine is also called alternative medicine. Sanliurfa has become one of the leading centers in the field of folk medicine since it is a cultural center from past to present. Today, with the development of modern medicine, the number of folk dentists has been reduced by fingers. People who practice folk medicine are usually people with religious beliefs. For this reason, the culture of prayer, vows and visits has increased over time. In this study, we examined the treatment methods used in ġanlıurfa's many regions. Although some applications are still used today, most of them have been used less often with the development of modern medicine and the proliferation of possibilities. Animal husbandry has been one of the main livelihoods of our geography and Anatolia throughout history. There are various diseases in animals as well as in humans. Many treatment modalities have been developed to treat these diseases, and most of these methods are still in use today. Folk medicine and folk veterinary medicine are a tradition that is passed on from generation to generation. With tradition called hand-giving, physicians have transferred their knowledge to their children. Our work consists of five parts. In the first part, we discussed the definition and history of folklore. In the second part, we gave information about the characteristics and the history of the region we studied. The third part is the study of the practice of folk medicine, which is the subject of our thesis. In the fourth chapter, we have examined the subject of Folk Veterinary, a subdivision of the folk medicine. The final part is the result section. Here we made the assessment of the results we have obtained. In the bibliography, all the resources we use are given according to the Institute format.

ÖZ: Tezimizin amacı ġanlıurfa yöresinde kullanılan Halk Hekimliği tedavi yöntemlerini ortaya çıkarmak ve unutulmaya yüz tutmuĢ bilgileri yazılı bir kaynak ile kalıcı bir hale getirmektir. Ġlk insandan bu yana hastalıklar hep süregelmiĢtir. Ġnsanlar da bu hastalıklara çareler üretebilmek amacıyla birçok yöntem denemiĢlerdir. Bu yöntemler günümüz tıp bilimin temelini oluĢturmuĢtur. KuĢaktan kuĢağa aktarılan bilgilerden bazıları geliĢmiĢ tıp bilimine rağmen hala kullanılmaktadır. Bunun sebebi okur-yazar oranının hala istenen düzeyde olmaması ve sağlık kuruluĢlarının hala bazı bölgelere ulaĢmamıĢ olmasıdır. Bir baĢka neden de insanımızın aradığı Ģifayı modern tıp ile bulamamasıdır. Halk hekimliği günümüzde alternatif tıp olarak da adlandırılmaktadır. ġanlıurfa geçmiĢten günümüze kadar bir kültür merkezi olması dolayısıyla halk hekimliği konusunda da öncü merkezlerden birisi olmuĢtur. Günümüzde modern tıbbın geliĢmesi ile halk hekimi sayısı parmakla sayılacak kadar azalmıĢtır. Halk hekimliği yapan kiĢiler genellikle dini itikadı yüksek olan kiĢilerdir. Bu nedenle zamanla dua, adak ve ziyaret kültürü artmıĢtır. Bu çalıĢmamızda ġanlıurfa‟nın birçok yöresinde kullanılan tedavi yöntemlerini inceledik. Bazı uygulamalar günümüzde hala kullanılsa da modern tıbbın geliĢmesi ve imkanların çoğalmasıyla birçoğu daha az kullanılmıĢtır. Hayvancılık tarih boyunca coğrafyamızın ve Anadolu‟nun temel geçim kaynaklarından biri olmuĢtur. Ġnsanlarda olduğu gibi hayvanlarda da çeĢitli hastalıklar görülmektedir. Bu hastalıkları tedavi edebilmek için birçok tedavi yöntemi geliĢtirilmiĢtir ve bu yöntemlerin çoğu günümüzde hala kullanılmaktır. Halk hekimliği ve halk veterinerliği kuĢaktan kuĢağa aktarılan bir gelenek unsurudur. El verme denilen gelenek ile hekimler bilgilerini çocuklarına aktarmıĢlardır. ÇalıĢmamız beĢ bölümden oluĢmaktadır. Birinci bölümde Halkbilimi tanımı ve tarihçesini ele aldık. Ġkinci bölümde çalıĢma yaptığımız bölgenin özellikleri ve tarihçesi hakkında bilgi verdik. Üçüncü bölüm tezimizin konusu olan halk hekimliği uygulamalarının incelendiği bölümdür. Dördüncü bölümde halk hekimliğinin bir alt dalı olan halk veterinerliği konusunu inceledik. Son bölümümüzde ise elde ettiğimiz bütün verileri ve hala kullanımda olan tedavi yöntemlerini, incelememiz sonucunda elde ettiğimiz bilgilerin değerlendirmesini yaptık. Kaynakça bölümünde, yararlandığımız tüm kaynaklar enstitü formatına göre verilmiĢtir.
Türk Dili ve Edebiyatı Dalında Yüksek Lisans Tezidir. Tez (Yüksek Lisans)--Doğu Akdeniz Üniversitesi, Fen ve Edebiyat Fakültesi, Türk Dili ve Edebiyatı Bölümü, 2018. Tez Danışmanı: Yard. Doç. Dr. Elnara Bashirova
Keywords: Türk Dili ve Edebiyatı; Halk Hekimliği--Şanlıurfa (Türkiye); Halkbilimi; Halk Hekimliği; Halk Veterinerliği; Şanlıurfa; Folklore; Folk Medicine; Folk Veterinary; Şanlıurfa